A Squeeze Pack and Transfer Algorithm-based Efficient Framework for Optimized Network Data Transfer in IoT Applications - Preet , Shiv; Sharma , Chirag; Garg, Rachit (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The wireless network is the driving force behind the new world's economy, and its invasion has spread far beyond Earth in an interplanetary network using satellites. Wireless networks' productivity must be ur-gently improved because they are prone to signal attenuation, slower transfer speeds, complete signal un-availability due to weather, and overcrowding of connected users. Due to the towers' remote position, ex-cessive latency is also an issue, as is the enormous magnitude of data transfer that comes with the big data revolution. The antiquated TCP protocol, which is ineffective for low consumption and limited storage IoT items as data buffer is insignificant in such devices, is another problem for IoT applications. A novel SPT (Squeeze Pack and Transfer) algorithm has been proposed to increase mobile network productivity and reduce storage by more than 90% for data files. Binary patterns, rather than conventional textual symbols compress data, resulting in a higher compression ratio and faster compression speed. The suggested algo-rithm will significantly improve network performance while also facilitating efficient data transfer for IoT devices with limited storage. Many researchers confront issues such as low compression ratios and re-stricted support for multiple data formats from generic compression. All of these concerns are addressed by the proposed method.